Peran Siswa Perempuan dalam Pembelajaran Ensambel Musik - Lakusa, Nicholas Ferdeta; Nayati, Widya (Pusat Studi Wanita dan Keluarga UGM, 2023)
Music ensembles are one of the methods most often used in music education in schools. This research aims to determine the role of female students in ensemble groups from two aspects, namely affective and psychomotor. These group activities are essential for the development of the spirit of togetherness, perseverance and cooperation—activities that are very important for student development. Understanding the group of female students and male students in ensemble activities really needs to be done by trainers / teachers because the self-development of girls and boys will be different, so when they are gathered to work together, special handling is needed to produce cohesion in work. Data was collected by observing the implementation of ensemble learning. The subjects of this research were 32 students in class VII-D of SMP Negeri 2 Mlati. The results of the research show that there are differences in the interaction process in practice and the results of music playing between groups that have female members and those that do not. The presence of female students makes the practice process more dynamic, giving rise to creativity when playing a song. The results of this study can be used as evaluation material for an educator in planning a more meaningful ensemble learning.